In situ observation of tungsten plasma-facing components after the first phase of operation of the WEST tokamak. (6th September 2021) - Diez, M.; Corre, Y.; Delmas, E.; Fedorczak, N.; Firdaouss, M.; Grosjean, A.; Gunn, J.P.; Loarer, T.; Missirlian, M.; Richou, M.; Tsitrone, E.; WEST Team, the
Abstract: After three years of operation (2017–2019) and four experimental campaigns (C1 to C4), the first phase of operation of the WEST tokamak has now come to an end. During that period, WEST has operated with tungsten coated copper-based and carbon-based plasma facing components in order to comply with a full metallic environment. A set of components, called plasma facing units, using ITER tungsten monoblock technology was also installed onto one sector of the lower divertor to test their behaviour in a real tokamak environment. This paper gives an overview of the ageing behaviour of these components during in situ visual inspections. It is shown that tungsten coatings are in a good condition after 3 years of operation but are prone to delamination in the areas dominated by off-normal events such as runaway electrons or arcing. For this reason, the W coated carbon tiles of the outer limiter were replaced by bulk W tiles after the C3 campaign. As for the bulk tungsten ITER-like components, damage such as melting and cracking was mainly observed on the monoblock edges exposed to the parallel heat flux. The first observations show that the damage formed during C3 on the tungsten monoblocks did not evolve during C4, which leads to believe that it results from singular events rather than continuous heating due to steady state operation.